Atypical Hemolytic Uremic Syndrome Presenting as Acute Heart Failure—A Rare Presentation: Diagnosis Supported by Skin Biopsy. (April 2019) - Kichloo, Asim; Chugh, Savneek Singh; Gupta, Sanjeev; Pandav, Jay; Chander, Praveen
Atypical hemolytic uremic syndrome (aHUS) is a rare disorder of uncontrolled complement activation that manifests classically as anemia, thrombocytopenia, and renal failure, although extrarenal manifestations are observed in 20% of the patient most of which involving central nervous system, with relatively rare involvement of the heart. In this article, we report the case of a 24-year-old male with no history of heart disease presenting with acute systolic heart failure along with microangiopathic hemolytic anemia, thrombocytopenia, and acute kidney injury. Given his presentation of thrombotic microangiopathy (TMA), along with laboratory results significant for low haptoglobin, platelets, hemoglobin, C3, C4, CH50, and normal ADAMTS13 levels, with no diarrhea and negative STEC polymerase chain reaction in stool, aHUS diagnosis was established with strong clinical suspicion, and immediate initiation of treatment was advised. Kidney biopsy to confirm diagnosis of aHUS was inadvisable because of thrombocytopenia, so the skin biopsy of a rash on his arm was done, which came to be consistent with thrombotic microangiopathy. Our case highlights a relatively rare association between aHUS and cardiac involvement, and the use of skin biopsy to support diagnosis of aHUS in patients who cannot undergo renal biopsy because of thrombocytopenia.